2021
DOI: 10.1111/pops.12784
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Consequences of Having a Political Reputation in Class

Abstract: The study examined the individual characteristics and consequences of psychological group processes that may lead some students to gain a reputation for being politically knowledgeable and verbal in class (a political reputation). Two normal samples of Swedish students were used, 13-year-olds (N = 835) and 16-year-olds (N = 795). Longitudinal data over one year were analyzed and showed that youths' political reputation in class is established very early. Cross-sectional predictions showed that political inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This study focuses on the psychological group processes in normal classrooms that lead some students to gain a reputation as politically knowledgeable and verbal in class. In the earlier study by Stattin and colleagues (2021), political reputation in class was not predicted by students' perceptions that teachers encouraged attendance to sociopolitical topics or the students' receptiveness to teachers' sociopolitical communications. This suggests that the group dynamics that contribute to a social reputation as politically knowledgeable and verbal may operate rather independently of the ways that schools conduct civic education (cf.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…This study focuses on the psychological group processes in normal classrooms that lead some students to gain a reputation as politically knowledgeable and verbal in class. In the earlier study by Stattin and colleagues (2021), political reputation in class was not predicted by students' perceptions that teachers encouraged attendance to sociopolitical topics or the students' receptiveness to teachers' sociopolitical communications. This suggests that the group dynamics that contribute to a social reputation as politically knowledgeable and verbal may operate rather independently of the ways that schools conduct civic education (cf.…”
Section: Discussionmentioning
confidence: 72%
“…These findings agree well with other studies that have used peer nominations and found that classmates' nominations of characteristics like aggression, shyness, leadership, achievement orientation, peer victimization, and immaturity show 1‐ or 2‐year stabilities of over .50 even by age 9 or 10 (Aleva et al, 2017; Bukowski & Newcomb, 1984; Liu et al, 2014). In Stattin and colleagues' study (2021), predictions over 1 year revealed that political reputation in class positively predicted the adolescents' political interest and internal political efficacy in both cohorts. Apparently, the group dynamics in classes whereby some students obtain a political reputation seem to have at least short‐term consequences for these students.…”
Section: Social Identity and Reputationmentioning
confidence: 96%
See 3 more Smart Citations